WANPRESTASI DAN PENYELESAIANNYA DALAM PERJANJIAN KREDIT PEMILIKAN RUMAH (KPR) PADA BANK BTN CABANG SINGARAJA BALI - I Gede To Kaesar Nero (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTThe process of home ownership with mortgage system (KPR) raises a variety of issues that need to get a settlement solution. One of the problems that arise in the mortgage agreement is the issue of loan guarantees to be provided by the bank and its binding ordinances. Guarantees the mortgages (mortgage) is the home to be purchased by the customer. Issues that arise in terms of the guarantee is that at the time the loan is realized, it means the bank has disbursed funds to pay for the house, ownership of land and the house has not been transferred to the customer's credit recipients, so the banks have to wait for the process behind the name and the binding process loan guarantees for housing and land. Other issues that arise in the implementation of the mortgage is in default. Defaulting debtors is done with a variety of forms and the reasons why credit recipients are in default. One form of credit default recipient is taken not to pay their debts or repay the installments of the reasons the quality is not in accordance with the specifications that have been offered by the developer / developer at the time prior to the transaction.Key Words : Tort, Credit Agreement, Owned Home Loan